Portfolio Optimization in Post Financial Crisis of 2008-2009 in the Mongolian Stock Exchange - Lee, Cheng-Wen; Gankhuyag, Dolgion (Metris: Jurnal Sains dan Teknologi, 2020)
In this study, we present the Mongolian stock market’s performance post phenomenal financial crisis of 2008-2009, opportunities to invest and the risks problems. For analysis of the study, we used financial portfolio optimization models with restricted structure, mathematical statistic methods and financial methods. First, we considered about portfolio optimization in the Mongolian Stock Exchange using Markowitz’s modern portfolio theory and Telser’s safety first model. We used MSE weekly trading data chosen 50 most traded stocks out of 237 stocks listed at the MSE between 2009 and 2013. We generated 50 weeks mean-variance portfolio and safety first portfolio for 2014 and discussed. We considered weekly investment in the MSE using mean-variance portfolio andsafety first portfolio. The mean-variance portfolio has the best performance of weekly portfolio return with average weekly return and cumulative return. We found stable portfolio against investing risk and did back-test the result. For prospect investors in the MSE, we suggest invest and earn high return in the MSE.